Hubungan antara Perceived Organizational Support dengan Kinerja Karyawan Bidang Produksi di PT Batanghari Barisan Padang - Zurriyati Zurriyati; Krisnova Nastasia; Ria Okfrima (Fakultas Psikologi, Universitas Putra Indonesia YPTK Padang, 2020)
This study aims to determine the relationship between perceived organizational support and employee performance in production at PT Batanghari Barisan Padang. The independent variable in this study is perceived organizational support and the dependent variable is Performance. The measuring instrument used in this study is the scale of perceived organizational support and performance. The sampling technique in this study uses a saturated sample technique. The sample in this study was 81 employees of the production field of PT Batanghari Barisan Padang. The validity and reliability test in this study uses the Cronbach Alpha technique. The results of the validity coefficient on the scale of perceived organizational support move from rix = 0.310 to rix = 0.809 with a reliability coefficient of α = 0.883 while on the scale of moving performance from rix = 0.316 to rix = 0.803 with a reliability coefficient of α = 0.864. Based on data analysis, a correlation value of 0.515 was obtained with a significance level of 0.000, which means the hypothesis was accepted. This shows that there is a significant relationship between perceived organizational support and the performance of employees in the production sector at PT Batanghari Barisan Padang. The effective contribution of the variable perceived organizational support for performance by 30%.